Pemanfaatan Tanaman Kiambang sebagai Agen Fitoremediasi untuk Penetralan Air Asam Tambang - Hisni Rahmi; Restu Permana; Nelsy Mariza Syahyuda; Restu Juniah (Pusat riset dan Inovasi Nasional, 2025)
The pH value parameter in the mineral acid water of a coal mining company in South Sumatra is below the set environmental quality standards. The results of measuring the pH value using a pH meter at the inlet are 4.9 which is still below the environmental quality standard of 6-9. Therefore, it is necessary to make efforts to manage the environment before water is discharged into water bodies, one of which is by utilizing kiambang plants as phytoremediation agents in neutralizing mine acid water. This study aims to analyze changes in mine acid water quality and analyze the effectiveness of mine acid water neutralization. The initial quality of mine acid water for pH parameters was 4.9 TDS of 376 mg/l, Fe of <0.1 mg/l, and Mn of 3 mg/l. After the phytoremediation process, the water quality change for pH parameters was 6.6 and Mn was 0.05 mg/l. The neutrality effectiveness of mine acid water increased the pH by 34.69% and the effectiveness of reducing Mn levels by 98.33%. This kiambang plant can be a recommendation for phytoremediation agents for companies considering its availability around the company